2018
DOI: 10.1590/0102-672020180001e1380
|View full text |Cite
|
Sign up to set email alerts
|

The Critical View of Safety Prevents the Appearance of Biliary Injuries? Analysis of a Survey

Abstract: Background: The risk of bile duct injury (BDI) during cholecystectomy remains a concern, despite efforts proposed for increasing safety. The Critical View of Safety (CVS) has been adopted promoting to reduce its risk. Aim: To perform a survey to assess the awareness of the CVS, estimating the proportion of surgeons that correctly identified its elements and its relationship with BDI. Methods: An anonymous online survey was sent to 2096 surgeons inquiring on their common practices during cholecystectomy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Indeed, in the Netherlands the CVS is included in the national guidelines for LC [8]. However, despite accepting the core CVS principles, a significant proportion of surgeons still has difficulty in correctly recognising all three criteria (17% in the Netherlands, 25% in Latin America) [9, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the Netherlands the CVS is included in the national guidelines for LC [8]. However, despite accepting the core CVS principles, a significant proportion of surgeons still has difficulty in correctly recognising all three criteria (17% in the Netherlands, 25% in Latin America) [9, 52].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most surgeons (88.3%) reported that they knew about CVS but only 11.5% knew about it correctly ( 38 ). A survey conducted in South America comprising 446 surgeons showed that the percentage of surgeons who correctly identified all three criteria of CVS was 21.8% ( 39 ). A large-sample survey conducted in the Netherlands, where CVS is routinely required during LC, indicated that although 98.2% of the surgeons claimed that they incorporated the CVS technique into daily practice, only 16.9% of the surgeons correctly selected all three criteria of CVS ( 40 ).…”
Section: Discussionmentioning
confidence: 99%